2017
DOI: 10.1155/2017/5878614
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Common Bile Duct Exploration for Retrieval of Impacted Dormia Basket following Endoscopic Retrograde Cholangiopancreatography with Mechanical Failure: Case Report with Literature Review

Abstract: Dormia baskets are commonly used during endoscopic retrograde cholangiopancreatography (ERCP). One complication is basket retention, through impaction with a gallstone or wire fracture. We describe a case where the external handle of the basket snapped causing retained basket plus large gallstone impacted in the common bile duct (CBD). Following laparoscopic cholecystectomy, laparoscopic CBD exploration allowed direct stone fragmentation under vision with the choledochoscope. Fragments were removed using a cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The retained basket has been retrieved by a variety of strategies such as extracorporeal shock wave lithotripsy (ESWL), sphincterotomy and balloon dilatation, rescue mechanical lithotripter, exchange of metal wires or metal sheaths or choledochotomy – either via laparotomy or laparoscopic approach. [ 5 6 ] ESWL utilises laser lithotripsy to fragment the stones that further aid in retrieving the impacted dormia. However, this needs expertise and several sittings to achieve complete duct clearance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The retained basket has been retrieved by a variety of strategies such as extracorporeal shock wave lithotripsy (ESWL), sphincterotomy and balloon dilatation, rescue mechanical lithotripter, exchange of metal wires or metal sheaths or choledochotomy – either via laparotomy or laparoscopic approach. [ 5 6 ] ESWL utilises laser lithotripsy to fragment the stones that further aid in retrieving the impacted dormia. However, this needs expertise and several sittings to achieve complete duct clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, endoscopic rescue has been attempted in experienced centres, but it is often difficult to catch the tip of impacted dormia basket and can be associated with risk of perforation, bleeding and need for multiple sessions. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An unusual but possible complication is Dormia basket impaction or Traction cable breakage when removing CBD stones. An expert study reported that the complication rate associated with the use of the Dormia basket, due to a stone of hard or large consistency (> 1 cm), is a complication ranging from 0.8 to 6% of cases [ [5] , [6] , [7] ]. Therefore, it deserves an urgent resolution; however, at the moment, there is no consensus on the optimal technique or the behavior to follow for the resolution of this complication [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%